Indigenous Peoples and the Struggle in Defense of the São Francisco River (Sustainability in Debate, 2013)
The objective of this article is to reflect about the indigenous people who live in the São Franciscoriver area and how they act in defense of its preservation. In a time that agribusiness is becomingstronger and dams and the canal to divert that river are in construction, many social andenvironmental conflicts have arisen in that region. The Environment Impact Studies do not takein account the dynamic of those indigenous peoples with their land and how they relate to theSão Francisco river. Based on bibliographical research about the conflicts that come with thoseprojects, we conclude that those projects repeat the mistakes from the past in its relation withthose indigenous people.